Moderate Fluid Shear Stress Regulates Heme Oxygenase-1 Expression to Promote Autophagy and ECM Homeostasis in the Nucleus Pulposus Cells - Chen, Sheng; Qin, Lei; Wu, Xiaohao; Fu, Xuekun; Lin, Sixiong; Chen, Di; Xiao, Guozhi; Shao, Zengwu; Cao, Huiling (Frontiers in Cell and Developmental Biology, 2020)
In vertebrate，the nucleus pulposus (NP), which is an essential component of the intervertebral disc, is constantly impacted by fluid shear stress (FSS); however, molecular mechanism(s) through which FSS modulates the NP homeostasis is poorly understood. Here we show that FSS regulates the extracellular matrix (ECM) homeostasis in NP cells. A moderate dose of FSS (i.e., 12 dyne/cm2) increases the sulfated glycosaminoglycan (sGAG) content and protein levels of Col2a1 and Aggrecan and decreases those of matrix metalloproteinase 13 (MMP13) and a disintegrin and metalloproteinase with thrombospondin motif 5 (ADMATS5) in rat NP cells, while a higher dose of FSS (i.e., 24 dyne/cm2) displays opposite effects. Results from RNA sequencing analysis, quantitative real-time RT-PCR analysis and western blotting establish that the heme oxygenase-1 (HO-1) is a key downstream mediator of the FSS actions in NP cells. HO-1 knockdown abolishes FSS-induced alterations in ECM protein production and sGAG content in NP cells, which is reversed by HO-1 induction. Furthermore, FSS activates the autophagic pathway by increasing the LC3-II/LC3-I ratio, Beclin-1 protein level, and formation of autophagosome and autolysosome and thereby regulates ECM protein and sGAG production in a HO-1 dependent manner. Finally, we demonstrate that the intraflagellar transport (IFT) 88, a core trafficking protein of primary cilia, is critically involved in the HO-1-mediated autophagy activation and ECM protein and sGAG production in FSS-treated NP cells. Thus, we for the first time demonstrate that FSS plays an important role in maintaining ECM homeostasis through HO-1-dependent activation of autophagy in NP cells.